UPAYA PENCEGAHAN DBD DENGAN GERAKAN SATU RUMAH SATU JUMANTIK DALAM MEWUJUDKAN MASYARAKAT PEDULI SEHAT - Willia Novita Eka Rini; Vinna Rahayu Ningsih (Prodi Ilmu Kesehatan Masyarakat, FKIK Universitas Jambi, 2020)
DHF is a health problem whose number of sufferers continues to increase and the spread is wider.DHF is an acute disease with clinical manifestations of bleeding that can lead to shock and lead to death. Various efforts have been carried out by the government such as the eradication of plural larvae through fogging, mass abasiasi movements, but this has not been optimal enough. Efforts to eradicate DHF can succeed if there is an active role from the entire community. To deal with dengue cases and their prevention special assistance is needed to work periodically in the environment. The community-run PSN program was then monitored by a larva (jumantik) observer to run effectively. The tasks of the jumantik include ensuring the existence of Aedes Aegepty mosquito larvae. A place that is suspected of being a breeding ground for mosquito larvae such as water reservoirs or clear puddles is not grounded, because the Aedes mosquito aygepty likes to lay eggs and lay their eggs in puddles that are clean and not directly grounded. In addition, jumantik also educates and helps implement 3M Plus in the home environment. The results of this service were obtained by jumantik cadres who were in charge of supervising the mosquito larvae in the house so that the dengue cases in Jambi City could be eradicated.